1979
DOI: 10.1055/s-0028-1097293
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structure Elucidation of Isovaltral, a Decomposition Product of Isovaltrate

Abstract: Decomposition products of the valepotriates are formed during the e1,ution process on columns using silica and alumina as stationary phase. Some of these decomposition products were identified as baldrinal and homobaldrinal and a new one, isovaltral, was found. the valepotriates were isolated by T H I E~ [ I 4 1 from some dried roots of Valeriana species and from Valeriana tinctures. The most important of these decomposition products are baldrinal and homobaldrinal, which are formed from valtratelacevaltrate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…As expected, a notable NOE correlation of H-1 and H-9 could be discerned in the NOESY spectrum of 1, S. Lin et al 2 in full support of this assignment. Since isovaltrate could successfully convert into isovaltral during the elution process under the influence of acid and heat [13], the stereochemistry of C-1, C-8, and C-9 still remained the 1S, 8R, 9S configuration. On the basis of these data and chemical transformation grounds, the structure of 1 was consequently established as shown.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…As expected, a notable NOE correlation of H-1 and H-9 could be discerned in the NOESY spectrum of 1, S. Lin et al 2 in full support of this assignment. Since isovaltrate could successfully convert into isovaltral during the elution process under the influence of acid and heat [13], the stereochemistry of C-1, C-8, and C-9 still remained the 1S, 8R, 9S configuration. On the basis of these data and chemical transformation grounds, the structure of 1 was consequently established as shown.…”
Section: Resultsmentioning
confidence: 95%
“…The residue (630 g) was suspended in H 2 O (1500 ml) and then partitioned with EtOAc (5 £ 1000 ml). The EtOAc fraction (420 g) was chromatographed over silica gel, Sephadex LH-20, and preparative TLC to isolate (Table 1), the 1 H NMR, 13 C NMR and DEPT spectra of 1 in CDCl 3 showed the same iridoid nucleus resonances as isovaltral, a decomposition product of isovaltrate [13], exhibiting signals for an a,b- . These spectroscopic data revealed that 1 was the isovaltral analog but with one b-(acetoxy) isovaleroxy and acetoxy groups substituted at C-1 and/or C-8 and/or C-11.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isovaltral (76) is a degradation product of valtrate 58 (71). The molecular ion produces a low peak and undergoes loss of an isovaleroxy radical, than acetic acid and a hydrogen atom.…”
Section: Ch3mentioning
confidence: 99%